Handbook of research on green ICT [ technology, business, and social perspectives - Unhelkar, Bhuvan (Gale virtual reference library, 2010)
"This handbook coalesces worldwide investigations, thoughts, and practices in the area of Green ICT, covering the technical advances, methodological innovations, and social changes that result in enhancements and improvements in business strategies, social policies, and technical implementations" -- Provided by publisher